2016
DOI: 10.1097/iae.0000000000001085
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal Capillary Density After Plaque Radiotherapy for Choroidal Melanoma

Abstract: Optical coherence tomography angiography allows qualitative and quantitative analysis of parafoveal capillary density. After plaque radiotherapy for choroidal melanoma, in eyes with normal macular features on ophthalmoscopy and optical coherence tomography, there is a statistically significant decrease in parafoveal capillary density and logMAR visual acuity in irradiated eyes compared with fellow eyes. These subclinical ischemic findings represent the commencement of radiation maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
2
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 30 publications
0
34
2
11
Order By: Relevance
“…Shields et al 14 have reported a decreased capillary density in both plexuses, as well as FAZ enlargement. Finally, Say et al 25 have reported decreased capillary density in irradiated eyes without clinically patent maculopathy.…”
Section: Discussionmentioning
confidence: 94%
“…Shields et al 14 have reported a decreased capillary density in both plexuses, as well as FAZ enlargement. Finally, Say et al 25 have reported decreased capillary density in irradiated eyes without clinically patent maculopathy.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, OCT-A is the most sensitive method with which to detect radiation maculopathy [3,13]. In fact, in a recent study of 65 patients, Shields et al [14] identified parafoveal changes on OCT-A.…”
Section: Discussionmentioning
confidence: 99%
“…Say et al and Cennamo et al quantified total vascular area using 3×3mm and 6×6mm binarized en-face images, respectively. (14, 15) Both demonstrated significant reduction in vessel area density in irradiated eyes compared to fellow eyes. Although the capillary densities in these previous studies were estimated as vessel area density, our preferred method for estimating capillary density is the skeletonized density (VSD).…”
Section: Discussionmentioning
confidence: 90%
“…To date, there have been a few studies that employ OCTA to assess microvascular changes in RR. Two recent studies used binarized OCT angiograms to demonstrate a decrease in parafoveal (14, 15) and peripapillary capillary (16, 17) density in irradiated eyes compared to fellow eyes. To our knowledge, no studies have performed longitudinal analysis to identify early microvascular changes (prior to 1 year) in treated eyes, nor have any used OCTA to explore a possible spatial correlation between these changes and radiation dose.…”
Section: Introductionmentioning
confidence: 99%